2020
DOI: 10.1055/s-0040-1712517
|View full text |Cite
|
Sign up to set email alerts
|

Limited Carpal Fusion in Kienböck's Disease: Early Results following Scaphocapitate Arthrodesis

Abstract: Background Kienböck's disease leading to progressive carpal collapse alters the wrist biomechanics leading to early arthritis and degenerative changes. Out of multiple surgical procedures present, no gold standard has been described. Scaphocapitate arthrodesis (SCA) is limited carpal fusion which shifts the loading axis toward radioscaphoid joint. This study presents the midterm clinical and radiological results of SCA in Kienböck's disease. Materials and Methods The data were reviewed from January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Six studies evaluated the postoperative VAS score. 11 , 15 , 19 , 20 , 21 , 22 Overall, there was a significant decrease in the postoperative VAS score ( Fig. 2 ; WMD, −3.6; 95% CI, −5.2 to −2.0; P =.00), with significant heterogeneity (I 2 = 96%; P =.00).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Six studies evaluated the postoperative VAS score. 11 , 15 , 19 , 20 , 21 , 22 Overall, there was a significant decrease in the postoperative VAS score ( Fig. 2 ; WMD, −3.6; 95% CI, −5.2 to −2.0; P =.00), with significant heterogeneity (I 2 = 96%; P =.00).…”
Section: Resultsmentioning
confidence: 94%
“…Scaphocapitate arthrodesis is a type of limited intercarpal fusion described by Pisano et al 10 and aims to reduce the axial load across both the radiolunate and lunocapitate joints. 11 Many studies have shown promising outcomes of this procedure because it is considered a predictable fusion with satisfactory results in preventing further collapse of the carpus, decreasing pain, and improving functional outcomes. 12 , 13 , 14 , 15 …”
mentioning
confidence: 99%
“…The benefit of PWA and PRC compared to total wrist arthrodesis, is the preservation of wrist motion. Biomechanical studies have shown that SC arthrodesis decreases the joint force across the radiolunate and lunocapitate joints by increasing the axial load directed to the radioscaphoid joint [ 6–7 ] and a recent clinical study has shown good short-term outcomes [ 8 ]. When comparing PWA, specifically SC arthrodesis, with PRC, Iorio et al.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for treatment of SC Arthrodesis concurs with the concept of Scaphotrapeziotrapezoid (STT) arthrodesis popularized by Watson et al [7,8] . Both STT and SC Arthrodesis aims to stop progression of carpal collapse and carpal-ulnar translation in order to preserve functional motion and provide pain relief [9] . In the STT fusion method we have to fuse 2 joints and it is more complex than scapho-capitate fusion in which a single joint has to be fused, in our case study we have done SCA.…”
Section: Discussionmentioning
confidence: 99%